Research On Cost-Benefit Analysis And Path Optimization Of Attracting And Retaining Talents In County-level Vocational Education - Hou Yuxi; Qin Yueqiong (Journal of Exploration of Vocational Education, 2025)
This study focuses on the cost-benefit imbalance of attracting and retaining talents in county vocational education, and reveals the key bottlenecks and optimization paths in the development of county vocational education by constructing the analytical framework of "cost-input-benefit-output-optimization-path", and by combining empirical analyses with cases of typical counties in the eastern, central and western regions. It is found that the marginal benefit of inputs for the integration of production and education (e.g., the construction of training bases by schools and enterprises) is the highest for county GDP (every 10,000 yuan of inputs in county A in the eastern part of the country drives the growth of 0.14 million yuan), while the hidden cost in less developed areas accounts for more than 60% of the total (e.g., the average annual replacement cost of county C in the western part of the country is 1.8 times of the visible cost due to the loss of talents). Generational differences in needs significantly affect the incentive effect, and the new generation of teachers is more sensitive to non-economic incentives (flexible working system, career development path) than traditional salaries. Based on this, we put forward the optimization strategy of "differentiated inputs, precise incentives, and dynamic adaptation", suggesting that the government should give priority to guaranteeing financial inputs in the field of high efficiency and benefit, and that institutions should implement the multi-dimensional incentives of "broadband salary+ and double-line promotion", and strengthen the policy through the synergy of legislation and digital monitoring, in order to solve the problem of VET in the county. It also suggests that the government give priority to guaranteeing financial investment in high-yield fields, institutions implement multi-dimensional incentives of "broadband salary and double-line promotion", and strengthen policies through legislative synergy and digital monitoring, so as to provide theoretical support and practical references for cracking the predicament of "attracting talents and retaining talents" in county VET.